Analysis and control of occupational safety risks using the HIRARC method in the Machining Workshop - Anwar, Roki Putra; Kurniawan, Andre; Mulianti; Abadi, Zainal (Researcher and Lecturer Society, 2024)
This qualitative study focuses on occupational safety and health in vocational school machining workshops to identify significant risks related to training practices. Workplace accidents are considered a serious threat to workers and equipment, potentially affecting productivity and environmental safety. Observations at several vocational schools, especially at SMK Negeri 1 Batipuh, showed low student awareness and compliance with OHS regulations, increasing the risk of risky behaviour and accidents. To address this, the research used the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method, which systematically identifies hazards, evaluates risks based on severity and likelihood, and proposes control measures. The research at SMK Negeri 1 Batipuh involved direct observation, interviews, and analysis of SOPs in the workshop, finding significant risk variations in workshop conditions, lathe operations, welding, material handling, hand tool use, and machine protection. The results highlighted the predominance of intermediate risks in all-hazards analyzed, emphasizing the importance of developing more effective risk management strategies. This research aims to reduce accidents and improve student safety during training by addressing existing OHS implementation gaps and implementing appropriate risk controls. In addition to filling a gap in the literature, this study provides practical insights for improving OHS practices in vocational schools.